Pengembangan Program Keterampilan Vokasional untuk Meningkatkan Produktivitas Kerja Bagi Siswa Tunarungu di SLB N Bekasi Jaya - Yulvia Sani; Heni Herlina (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
This research is based on the fact that many schools do not have a well planned and efficient program in conducting vocational learning skills. Developing such program will assist teachers on how to increase students’ productivity. This research uses two stages of method research: qualitative approach with descriptive method; and quantitative approach with descriptive method. The subjects are seven students of class XI with hearing barrier, and four custodian teachers in vocational skills. The result showed that: 1) Assessments about students interests, need, and abilty 2) Developing of skills program covers program draft, syllabus, conducting learning program, and program evaluation; 3) Program validating through expert judgment is well detailed and complete; 4) Students remarks on written test shows above of school standards, i.e., ≥ 75% to be concluded effective; 5) Program implementation designed by teachers showed that ≥ 95% had been done; and 6) Students are able to create various products independently.